1978
DOI: 10.2527/jas1978.4651338x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Protected Fat for Ruminants. IV. Plasma Lipid, Insulin and Depot Fat Composition of Lambs

Abstract: Fourteen crossbred lambs with an average weight of 29.4 kg were utilized to determine the influence of the nature and amount of dietary lipid intake on the qualitative and quantitative composition of the plasma lipid, carcass depot fats and plasma insulin levels. Formaldehyde treated casein-cottonseed oil (PCO) was supplemented at the rate of 8% (three lambs) and 12% (three lambs). Two groups of four lamb each were assigned to diets containing no added fat (control) and 8% unprotected cottonseed oil (8% CO).Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…The lack of significant variation of plasma glucose levels between the control and GSO supplemented diets is in accordance with the absence of effect of plant oils on plasma glucose in goat (Bernard et al 2005(Bernard et al , 2009. Several researchers showed that supplementation of diet with soybean oil, cottonseed oil and palm oil increased blood triglyceride and cholesterol contents (Hernandez et al 1978;Garcia et al 2003). Similarly, addition of sunflower oil at levels of 3.7% and 6.1% of diet DM increased triglyceride and total cholesterol levels in the plasma of Alpine (Bernard et al 2009) and Saanen (Razzaghi et al 2015) goats.…”
Section: Resultssupporting
confidence: 58%
“…The lack of significant variation of plasma glucose levels between the control and GSO supplemented diets is in accordance with the absence of effect of plant oils on plasma glucose in goat (Bernard et al 2005(Bernard et al , 2009. Several researchers showed that supplementation of diet with soybean oil, cottonseed oil and palm oil increased blood triglyceride and cholesterol contents (Hernandez et al 1978;Garcia et al 2003). Similarly, addition of sunflower oil at levels of 3.7% and 6.1% of diet DM increased triglyceride and total cholesterol levels in the plasma of Alpine (Bernard et al 2009) and Saanen (Razzaghi et al 2015) goats.…”
Section: Resultssupporting
confidence: 58%
“…In addition to the cAMP dependent pathway, there are several other pathways which can alter lipolysis in an adipocyte in response to various fatty acids. Phospholipase C (PLC) has been known to be activated by unsaturated fatty acids [35,36]. PLC cleaves phoshotidylinositol bisphosphate into diacylglyceride (DAG) and inositol 1,4,5-trisphosphate (IP3).…”
Section: Lipolysismentioning
confidence: 99%